2018
DOI: 10.1097/sle.0000000000000384
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Robotic Right Colectomy With Intracorporeal Anastomosis

Abstract: Through retrospective review of consecutive charts, we compare the short-term and long-term clinical outcomes after robotic-assisted right colectomy with intracorporeal anastomosis (RIA) (n=89) and laparoscopic right colectomy with extracorporeal anastomosis (LEA) (n=135). Cohorts were similar in demographic characteristics, comorbidities, pathology, and perioperative outcomes (conversion, days to flatus and bowel movement, and length of hospitalization). The RIA cohort experienced statistically significant: l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 25 publications
2
36
1
Order By: Relevance
“…[ 15 ] Another study concluded that the intracorporeal anastomosis may facilitate extraction of longer specimens with less trauma through smaller incisions. [ 30 ] Other laparoscopic right colectomy studies have confirmed shorter incisions and better cosmetic results for the intracorporeal approach. [ 22 , 24 , 25 , 28 ] Our study differs from prior published studies in that we performed a multi-center analysis with a larger sample size with results that may be more generalizable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 15 ] Another study concluded that the intracorporeal anastomosis may facilitate extraction of longer specimens with less trauma through smaller incisions. [ 30 ] Other laparoscopic right colectomy studies have confirmed shorter incisions and better cosmetic results for the intracorporeal approach. [ 22 , 24 , 25 , 28 ] Our study differs from prior published studies in that we performed a multi-center analysis with a larger sample size with results that may be more generalizable.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies demonstrate an advantage for the intracorporeal anastomosis for hospital LOS while others show no significant difference between groups. [ 14 17 , 21 25 , 27 , 28 , 30 , 31 ] This outcome is related to intestinal recovery time but there are other potentially confounding factors that contribute. We were unable to control for programs implementing Enhanced Recovery Pathways of varying degrees of standardization that decrease hospital LOS.…”
Section: Resultsmentioning
confidence: 99%
“…15,16 Another retrospective review in which the authors studied 89 patients undergoing robotic colectomy and 135 undergoing laparoscopic colectomy, found that robotic right colectomy with intracorporeal anastomosis was associated with shorter incision length, decreased rates of incisional hernia and anastomotic leak, and less EBL when compared with laparoscopic right colectomies with extracorporeal anastomosis. 17 A large retrospective multicenter study of 236 patients found no significant difference in conversion rates, morbidity or mortality rates, or average number of LN harvested when robotic right colectomy with intracorporeal anastomosis was compared with laparoscopic right colectomy with intracorporeal anastomosis and extracorporeal anastomosis. 18 In addition, robotic right colectomy with intracorporeal anastomosis showed significantly decreased time to flatus and shorter length of stay compared with laparoscopic right colectomies with extracorporeal anastomosis.…”
Section: Robotic Anastomosis After Right Colectomymentioning
confidence: 99%
“…A similar retrospective study compared the costs of a single surgeon's first 50 robotic versus laparoscopic rectal resections. 58 The study also compared operative times and costs as a function of experience within the robotic group, separating the 50 cases into three phases: the initial learning curve (cases [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], competent period (cases 20-40), and experienced phase (cases 41-50). On average, the operative times and overall costs were significantly higher in the robotic group than in the laparoscopic group.…”
Section: Costs Of Robotic Colorectal Surgerymentioning
confidence: 99%
“…Intracorporal anastomosis According to current literature, re-establishing intestinal continuity by intracorporal anastomosis in colon surgery is supposedly superior to extracorporal anastomosis in terms of return of bowel function, bowel obstruction, and hospital discharge [33,34]. To choose the specimen extraction site independently from the surgical site can be helpful to reduce incisional hernia rates and to accomplish a better cosmetic result [35]. The formation of an intracorporal anastomosis, however, requires advanced surgical skills, e.g., precise handling and introduction of a stapler into the loose bowel segments and suturing to close the enterotomy site.…”
Section: Supplementary Considerations On Robotic Surgerymentioning
confidence: 99%